Maria Ulfah: Traces of Women’s Law in Building Indonesian Nations, 1938–1973 - Utami, Fazriani Putri; Fatiyah; Hafiz Salae (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study examines the multidimensional contributions of Maria Ulfah Santoso (1911–1988), a pioneering advocate for women’s rights in Indonesia, in advancing gender equality during the period of 1938–1973. Using qualitative historical methods, the research analyzes primary sources such as newspapers, organizational archives, and legal documents, alongside secondary literature. The findings reveal that Maria Ulfah utilized her legal expertise to reform discriminatory marriage laws, including the introduction of Taklik Talak (prenuptial agreements) to protect women’s rights within marriage. Her leadership in the Indonesian Women’s Congress and role as the nation’s first female minister (1946) expanded women’s political participation, laying the groundwork for policies such as the 30% legislative seat quota (Law No. 2/2008). Additionally, she established the Yayasan Hari Ibu (1953) and Yayasan Tenaga Kerja Indonesia (1970s) to advance women’s education and labor rights. These efforts integrated Islamic principles with progressive legal and institutional frameworks, shaping Indonesia’s gender equality landscape. The study concludes that Maria Ulfah’s multidimensional approach—spanning legal, political, and socio-economic domains—remains relevant to modern feminist movements. Further research should explore her international networks and the enduring impact of her policy advocacy.